Optimal location of wireless charging facilities for electric vehicles: Flow-capturing location model with stochastic user equilibrium. (September 2015) - Riemann, Raffaela; Wang, David Z.W.; Busch, Fritz
Highlights: Optimal location of facilities for wireless power transfer for electric vehicles. Formulation of a flow-capturing location problem with route choice incorporated. Reformulation of mixed integer nonlinear program to obtain the global optimum. Abstract: In this study, the optimal locations of a specific type of charging facilities for electric vehicles (EVs), wireless power transfer facilities, are investigated. A mathematical model has been developed to address this problem. The objective of the model is to locate a given number of wireless charging facilities for EVs out of a set of candidate facility locations for capturing the maximum traffic flow on a network. The interaction between traffic flow patterns and the location of the charging facilities is incorporated explicitly by applying the stochastic user equilibrium principle to describe electric vehicle drivers' routing choice behavior. Firstly, the problem is formulated into a mixed-integer nonlinear program, secondly a solution method is developed to obtain the global optimal solution of the linearized program. Numerical experiments are presented to demonstrate the model validity.